MicroRNAs in nasopharyngeal carcinoma - Spence, Tara; Bruce, Jeff; Yip, Kenneth W.; Liu, Fei-Fei (Chinese Clinical Oncology; Vol 5, No 2 (April 19, 2016): Chinese Clinical Oncology (Nasopharyngeal Carcinoma-Guest Editors: Joseph Wee, Yoke-Lim Soong, Melvin Chua), 2016)
It is becoming increasingly evident that aberrantly expressed microRNAs (miRNAs) are responsible for a number of disease processes, including cancer initiation and progression. miRNAs have been implicated as key players in numerous neoplasms, including nasopharyngeal carcinoma (NPC). Functionally, deregulation of miRNAs that act either as tumour suppressors or oncogenes results in numerous cancer-associated phenomena, including changes in proliferation, migration, and cell survival. Furthermore, miRNA expression has been associated with chemoresistant or radioresistant phenotypes; highlighting the importance of miRNAs in mediating oncogenic processes. Prognostic and predictive miRNA signatures have been defined for a variety of cancer types, including NPC, whereby these signatures offer a potentially important clinical tool for assessing the disease state, as well as predicting treatment response and clinical outcome. Therefore, further examination and validation of miRNAs that are deregulated in NPC will provide insight into the fundamental drivers of this disease, which will aid in the identification of novel targeted treatments. This review summarizes recent advances in the study of miRNAs in NPC, with specific discussion on the role of miRNAs in NPC pathogenesis and the potential utility of miRNAs as prognostic biomarkers. Our increasing understanding of the role of miRNAs in NPC tumorigenesis and their application as novel biomarkers will undoubtedly prove useful in the stratification of future patients into clinically relevant treatment classifications, thereby improving and personalizing disease management.